Phase Transition Induced via the Template Enabling Cocoon‐like MoS2 an Exceptionally Electromagnetic Absorber. Issue 6 (3rd December 2022) - Fang, Jiefeng; You, Wenbin; Xu, Chunyang; Yang, Bintong; Wang, Min; Zhang, Jincang; Che, Renchao
Abstract: Structural engineering via the template method is efficient for micro‐nano assembling. However, only structural design and lack of composition control restrict their advanced application. To overcome this issue, applying a template to simultaneously realize the structural design and fine component control is highly desired, which has been ignored. In this study, a spinel‐shaped MoS2 heterostructure with controlled phase ratios of 1H and 2H phase is developed using the AlOOH template method. This work demonstrates that the MoS2 phase transition mechanism from 2H to 1T is substantially attributed to the close exposed crystal's surface and approximately accordant surface energy. The superiority and additional proof are provided based on density‐functional theory simulation, transmission electron microscope holography, etc. With an effective absorptance region of 6.3 GHz under a thickness of 1.4 mm, the reported samples present outstanding microwave absorption capacity. This is attributed to the beneficial coupled effect between the well‐designed structure and phase regulation. This work offers valuable insights into structural engineering and component regulation template methods. Abstract : Phase transition of MoS2 is realized under the layered AlOOH template with high lattice matching degree, prompting the conductivity of materials. The purity of 1T phase is regulated through the tunable lattice mismatch, which also expands the absorbing bandwidth to 6.3 GHz. Diverse heterojunctions benefiting from numerous crystal defects and interfaces are constructed to trigger more polarization phenomenon.